If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -1(-3 + -2q) + -10 = 0 -7 + (-3 * -1 + -2q * -1) + -10 = 0 -7 + (3 + 2q) + -10 = 0 Reorder the terms: -7 + 3 + -10 + 2q = 0 Combine like terms: -7 + 3 = -4 -4 + -10 + 2q = 0 Combine like terms: -4 + -10 = -14 -14 + 2q = 0 Solving -14 + 2q = 0 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 2q = 0 + 14 Combine like terms: -14 + 14 = 0 0 + 2q = 0 + 14 2q = 0 + 14 Combine like terms: 0 + 14 = 14 2q = 14 Divide each side by '2'. q = 7 Simplifying q = 7
| jx+my=x | | 7x^2+13x=2x^2-20x+14 | | 5a+15=35+23 | | 4(2v+3)-14v= | | 216=(2x+14)(x+4) | | 2s-3=60 | | 3x-3=4x-17 | | Ax+cx=b+d | | 3x+8-x=8+3x-6 | | 2y+2y-19y+35=0 | | 50.09+3.75x=800 | | 9x^2+12x=-9 | | 2.1+x=5.4 | | -3(4y-7)+2(3y+8)= | | (6x-4)+(4x+39)=180 | | 3x+4=17x+6 | | b-31b= | | x^2=(2x-7)(2x+13) | | -[5x-(3x+1)]=-6-[3(2x-4)-2x] | | (M-3)SQUARED(M-4)=0 | | 5Y^2-Y-12=0 | | 12(x+4)=14(x-2) | | 67+4x+15=90 | | X^2-Y^2-6X-4Y+4=0 | | -6a^6+4a^5-2a^4= | | -2-5cos(x)+6sin^2x=0 | | 2(X+X-7)=3(X+9+X+2+X-7) | | 5x+8x-20=0 | | -2+0.9+0.5(-2)=-2.1 | | (X)(-x)(-2x)= | | 3X^2-XY=0 | | (X)(2x)(y)= |